Lower Extremity Kinematics of the Y-Balance Test in Healthy and ACL Injured Adolescent Females - Alison Bulow; Alixandra Bellemare; Judy E Anderson; Jeff R S Leiter; Peter B MacDonald; Jason D Peeler (International Journal of Sports Physical Therapy)
# Background